In-Silico Analysis of Costunolide and Dehydrocostuslactone Interactions with NAFLD-Related Proteins - Pontjosudargo, Fransiska Ambarukmi; Priyadi, Hendri; Hermawanto, Agung; Bisri, Tatang (Chakra Brahmanda Lentera Institute, 2025)
Background: Non-alcoholic Fatty Liver Disease (NAFLD) is a growing health problem, but there is no standard drug for its treatment. Costunolide and dehydrocostuslactone are compounds found in Saussurea costus, exhibiting antioxidant activities that include anti-hepatotoxic, anti-inflammatory, and immunostimulant properties, which have been proven both in vivo and in vitro. This study aims to identify the bioactive ingredients of S. costus that affect NAFLD and explore its therapeutic targets through pharmacological networking. Various tissue databases were utilised to obtain the bioactive material from S. costus and identify potential therapeutic targets for NAFLD. Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to enrich the functions and molecular pathways of common targets. Methods: The analysis was conducted using a Structure-Activity Relationship (SAR) search to evaluate the biological potential of the studied compounds. The design of this study involved selecting costunolide and dehydrocostuslactone compounds as the subjects of analysis, with data collection conducted through public databases and relevant literature. SAR assessment was conducted using reporting standards, such as STITCH, to ensure transparency and reproducibility in the analysis. The score range used was 0-1, where the closer to 1, the better the value obtained. This process allows the identification of significant relationships between chemical structure and biological activity, as well as providing deeper insight into the potential of the compounds analysed. Thus, this method not only assesses the effectiveness of the compound but also provides a basis for further research in the development of therapy Results: The results of the Structure-Activity-Relationship (SAR) analysis were that the costunolide and dehydrocostuslactone compounds had scored <0.5 as a hepatoprotector and as a regulator of fat metabolism. The potential of these two compounds as TNF-alpha inhibitors and Interleukin-6 antagonists also shows a score <0.5. Conclusion: Costunolide and dehydrocostuslactone showed significant potential as anti-inflammatory agents and NF-κB transcription inhibitors. These findings indicate that both compounds may be promising candidates for NAFLD therapy, particularly through the mechanism of inhibition of the NF-κB transcription pathway. The implications of these results suggest the need for further studies to explore the efficacy and safety of these compounds in a clinical context, as well as their potential in the development of novel therapies for non-alcoholic fatty liver disease.